2015
DOI: 10.1111/1365-2435.12407
|View full text |Cite
|
Sign up to set email alerts
|

Moose browsing alters tree diversity effects on birch growth and insect herbivory

Abstract: Summary 1.Producer diversity is known to affect a wide range of ecosystem processes including plant growth and insect pest resistance. Consumers such as mammalian herbivores too have been shown to modify plant growth and insect herbivory by triggering changes in host plants. However, few studies have investigated whether consumer effects interact with plant species diversity effects on a focal plant. 2. To unravel consumer-diversity interactions, we recorded both the presence and intensity of winter browsing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
4
26
1
Order By: Relevance
“…As tree species richness increases, the presence of tree species differing in growth rates and foliage structure may result in less horizontal canopy space used and, thus, a more open canopy (Lang et al 2011). This has previously been shown in the Satakunta experiment, with canopy cover around birch trees decreasing with tree species richness (Muiruri et al 2015). As a result, artificial larvae may be more visible to birds when the focal trees are surrounded by heterospecifics, but these effects are likely to be restricted to small spatial scale and unlikely to manifest at plot level.…”
Section: Effects Of Tree Species Richness At Different Spatial Scalesmentioning
confidence: 61%
See 1 more Smart Citation
“…As tree species richness increases, the presence of tree species differing in growth rates and foliage structure may result in less horizontal canopy space used and, thus, a more open canopy (Lang et al 2011). This has previously been shown in the Satakunta experiment, with canopy cover around birch trees decreasing with tree species richness (Muiruri et al 2015). As a result, artificial larvae may be more visible to birds when the focal trees are surrounded by heterospecifics, but these effects are likely to be restricted to small spatial scale and unlikely to manifest at plot level.…”
Section: Effects Of Tree Species Richness At Different Spatial Scalesmentioning
confidence: 61%
“…In order to examine the role of structural complexity on bird predation, we used tree height measurements from 2011 where ten randomly chosen trees of each species were assessed in each experimental plot (Muiruri et al 2015). For each plot, we calculated a mean and standard deviation of tree heights, using data for all species combined in mixtures.…”
Section: Tree Height Variationmentioning
confidence: 99%
“…Growth–defence tradeoffs have often been implicated here as a possible explanation for negative (or positive) diversity effects on antiherbivore defences (Moreira et al ., ), with evidence emerging for reduced herbivore resistance in more diverse and productive stands (McArt & Thaler, ). However, in this study system, birch height growth is known to be consistent across the species richness gradient (Muiruri et al ., ), and thus, even if growth and antiherbivore defences are negatively correlated, we might not expect there to be any associated patterns in defensive traits across the diversity gradient.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, however, this area of research has developed independently of plant diversity studies, despite the fact that diversity effects on herbivory would be expected to influence plant induced responses and thus potentially lead to plant-mediated interactions among herbivores. For example, Muiruri et al [47 ] recently found that moose browsing on birch altered responses to tree species diversity by insect herbivores feeding on birch. Similarly, unpublished work by some of the co-authors of this paper indicates that genotypic diversity in Lima bean (Phaseolus lunatus) influenced damage by early-season herbivores (leaf chewers and aphids) and such effects in turn determined responses to diversity by late-season seed predators (Abdala-Roberts et al, unpublished data).…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%